Implementation of the Strategic Plan for Thai-Myanmar Border Tourism, Mae Sot District, Tak Province - จันทร์ประเสริฐ พิชิต (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
This research aims 1) to study the level of success in the implementation of the strategy, 2) to study the factors related to the success of the strategy implementation, and 3) to study the factors affecting the success of the strategic implementation. Sampling with a simple sampling method of 382 persons from the Tak Provincial Commissioner, employees of Mae Sot International Airport, hotel operator, tour operators, car operator, transportation operators in Tak province and selected 10 specific personnel from government agencies., senior manager, a five sets of questionnaires and structured interview and Correlation Coefficients and Multiple Regression Analysis were used. The research found that overview of success in strategic implementation of Thai-Myanmar border tourism are on the middle of 5 items 1) implementation of infrastructure development and facilities; 2) development and restoration of sustainable tourism; 3) product development of goods and the factor for tourism; 4) building confidence and promoting tourism; and 5) promoting the participation of the public sector, the people and the local government. Similarly, the promotion of Thai-Myanmar border tourism is moderate in average, with a high level of management and leadership, strategic plan, organization of learning, personnel development network and average corporate culture. The 8 tourism promotion factors are: 1) organization management 2) strategic plan 3) learning organization 4) network 5) leadership 6) staff performance 7) budget and 8) organizational culture related to the success of 96.6% of the strategies were operational and could explain the changes. The success of the strategic implementation was 93.1 percent. The first seven variables had a positive influence on the level of success at the .05 level.